2004
DOI: 10.1103/physrevc.70.065806
|View full text |Cite
|
Sign up to set email alerts
|

Nonuniform neutron-rich matter and coherent neutrino scattering

Abstract: Nonuniform neutron-rich matter present in both core-collapse supernovae and neutron-star crusts is described in terms of a semiclassical model that reproduces nuclear-matter properties and includes long-range Coulomb interactions. The neutron-neutron correlation function and the corresponding static structure factor are calculated from molecular dynamics simulations involving 40,000 to 100,000 nucleons. The static structure factor describes coherent neutrino scattering which is expected to dominate the neutrin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
214
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 154 publications
(217 citation statements)
references
References 22 publications
2
214
1
Order By: Relevance
“…For one, neutrino-pasta scattering helps determine the neutrino opacity in core collapse supernovae [6,7]. This is because supernova neutrinos have wavelengths comparable to pasta sizes and can scatter coherently from the pasta.…”
Section: Introductionmentioning
confidence: 99%
“…For one, neutrino-pasta scattering helps determine the neutrino opacity in core collapse supernovae [6,7]. This is because supernova neutrinos have wavelengths comparable to pasta sizes and can scatter coherently from the pasta.…”
Section: Introductionmentioning
confidence: 99%
“…Such a coherent neutrino-matter scattering is not only expected at low temperature, but even more in the possible occurrence of a critical point in the post-bounce supernova explosion, with the associated phenomenon of critical opalescence [4,5]. At variance with usual-matter properties, the expected increase in the static form factor was not observed in molecular-dynamics simulation of stellar matter at finite temperature [6]. This might be an effect of the Coulomb interaction which also acts in finite nuclei.…”
mentioning
confidence: 99%
“…Horowitz et al [18,19] studied these effects using the QMD technique but did not get a conclusive answer because they did not reproduce all the classical pasta shapes in their model. Sonoda et al [11] showed how pasta phases affect the neutrino transport cross section via weak neutral current using several nuclear models.…”
mentioning
confidence: 99%